The influence of utilitarian value, hedonic value, and online review on consumers’ satisfaction, trust, and repurchasing intention in e-commerce platforms - Dam Tri Cuong (Innovative Marketing)
E-commerce is the process of buying and selling goods via the use of various Internet platforms. E-commerce is crucial for companies that sell products or services online because it provides a reliable, easy, and 24/7 channel of commerce for clients worldwide. Therefore, this study examines the impact of utilitarian value, hedonic value, and online reviews on client satisfaction, trust, and repurchase intentions in e-commerce platforms. This study used the cognition-affect-conation paradigm as the theoretical basis for developing the research framework. A partial least squares method was used to verify the proposed model via Google Forms from August 2024 to September 2024, using data gathered from 297 participants who participated in online purchasing on e-commerce platforms in Vietnam. This research used an online survey because of its increasing popularity and its ease, convenience, and cost-effectiveness as a data-gathering method. The findings demonstrate that utilitarian value beneficially affected buyer satisfaction (β = .242, t = 4.121), trust (β = .202, t = 3.257), and repurchase intention (β = .221, t = 3.757). Likewise, hedonic value positively impacted consumer satisfaction (β = .281, t = 3.894), trust (β = .446, t = 6.122), and repurchase intention (β = .268, t = 3.753) on e-commerce platforms. Moreover, online client reviews had a beneficial impact on consumer satisfaction (β = .182, t = 3.463) and trust (β = .145, t = 2.570). Additionally, client satisfaction (β = .215, t = 4.064) and trust (β = .215, t = 4.064) positively influenced repurchase intention. AcknowledgmentThe author acknowledges Industrial University of Ho Chi Minh City that supported this study.